Tumor Necrosis Factor-α-Induced Protein 8-Like 2 Negatively Regulates Innate Immunity Against RNA Virus by Targeting RIG-I in Macrophages - Zou, Ziqi; Li, Mengyao; Zhou, Yunlian; Li, Jiaying; Pan, Ting; Lai, Lihua; Wang, Qingqing; Zhang, Lining; Wang, Qun; Song, Yinjing; Zhang, Yuanyuan (Frontiers in Immunology, 2021)
A systematic and flexible immunoregulatory network is required to ensure the proper outcome of antiviral immune signaling and maintain homeostasis during virus infection. Tumor necrosis factor-α-induced protein 8-like 2 (TIPE2), a novel immunoregulatory protein, has been extensively studied in inflammatory response, apoptosis and cancer. However, the function of TIPE2 in antiviral innate immunity is poorly clarified. In this study, we reported that the expression of TIPE2 declined at the early period and then climbed up in macrophages under RNA virus stimulation. Knockout of TIPE2 in macrophages enhanced the antiviral capacity and facilitated type I interferon (IFN) signaling after RNA virus infection both in vitro and in vivo. Consistently, overexpression of TIPE2 inhibited the production of type I IFNs and pro-inflammatory cytokines, and thus promoted the virus infection. Moreover, TIPE2 restrained the activation of TBK1 and IRF3 in the RLR signaling pathway by directly interacting with RIG-I. Taken together, our results suggested that TIPE2 suppresses type I IFN response induced by RNA virus through targeting RIG-I and blocking the activation of downstream signaling. These findings will provide new insights to reveal the immunological function of TIPE2 and may help to develop new strategies for clinical treatment of RNA viral infections.